Notas a respeito da multipropriedade imobiliária como nova modalidade do exercício do direito de propriedade - Rodrigues, Francisco Luciano Lima (2010)
This article tries to discuss the institution of timeshares. After apresentation of how this conception has evoluted among the different concepts of private property, the issue located the discussion of timeshares on European law, since the second half of the 19th. century, regarding the rights that can be atributed in favour of its owners, and which theories of its juridical nature that can be imputed to it. Also it will be discussed about possible reception of timeshares by the Brazilian law system.